Exploring Informal Digital Language Learning: How Learning Frequency Counts - Indrayani, Ninuk; Cahyono, Bambang Yudi; Mukminatien, Nur; Ivone, Francisca Maria (Journal of Languages and Language Teaching, 2024)
Facing globalization era, students tend to learn English informally. However, among the enormous studies on the use of informal learning, it was still inconclusive whether the time spent students dealt with their gadget really connected to English proficiency. This paper examines informal learning frequency in the area of English as a Foreign Language (EFL), particularly its contribution to students’ English proficiency. The study focuses on the discussions of time spent that students engage through English learning by the navigation of the digital application as part of informal learning. Correlation study was employed as the research design by collecting the data from 302 Indonesian university students through a survey. The findings showed positive yet low level of correlation, but reflect a description that students who preserve more time in the informal learning engagements made better improvement to English proficiency. The results of the study convinced that the frequent engagement with high agency of learning goal commitment is essential for achieving better English proficiency. Additionally, it adds an insight into how informal learning high frequency can make a unique contribution to EFL learners’ overall English outcomes and determine how teachers can provide necessary support to acknowledge the emerging progress of technology in education and modify their classroom practice through technology-enhanced language teaching with the intention of encouraging students’ autonomous learning with technology into language learning opportunities outside the classroom in order to enrich pedagogical insight of how informal digital learning can complement in-class and out-of-class learning.